Chapter Da citizenship a citizenshop: la de-universalizzazione della cittadinanza nell'epoca della globalizzazione - Russo, Pippo (Studi e saggi, 2023)
The article is focused on some transformative trends in citizenship profiles, all of them carachterized by a de-universalinzing dynamics. The starting point is T. H. Marshall's citizenship scheme, that is thought to be inspired on both individual and universal basis concerning the citizenship rights set. The changing produced by neo-liberal ideologies and globalization pressures is moving citizenship in a commodification sense, where citizenship profiles and rights are mediated by market and profiles are more and more personal and particularistic. Specifically, the focus of this essay is on skilled citizenship and citizenship by investment formulas.